Overhead ballistic ball throw performance: Youth vs. senior female national-level volleyball players - Kamutsri, T.; Choodam, C.; Ammat, A.; Khemtong, C. (Journal of Physical Education and Sport, 2024)
Background: The integration of inertial measurement units (IMUs) in medicine balls allows for the collection of metric derived data across various performance tests in athletes. Purpose: This study aimed to (1) compare overhead throw performance between senior and youth national-level female volleyball players using an IMU-equipped ballistic ball, and (2) document inter-limb asymmetry across different throwing metrics. A total of 31 national-level volleyball players participated in this study, comprising 16 seniors and 15 youths. A standing two-arm (ST-OH) and single (dominant and non-dominant arm; (ST-1OH) overhead medicine ball throw test was used to evaluate upper-body muscle performance (peak velocity, peak force, and peak power). Results: The senior group recorded significantly higher values for all metrics in ST-OH compared with the youth group (all P<0.01). For ST-1OH, the dominant-arm produced higher values across all ballistic ball metrics within both the senior (all P<0.01) and youth groups (all P<0.01), respectively. The senior group was able to produce a greater throw velocity in the dominant arm compared with the comparable arm in the youth group (P=0.026). For the non-dominant arm, a significant between-group inter-limb asymmetry was only noted for force (all P<0.037). Conclusion: Our findings support the use of the IMU-integrated medicine ball to develop the upper-body power of youth volleyball athletes based on meeting the benchmarking criteria of senior athletes. Moreover, our data suggest the medicine ball may be used to identify the presence of upper-body inter-limb asymmetry in volleyball players. Incorporating unilateral resistance training and usingtargeted training implements (i.e., bands, medicine ball, ballistic ball) should be employed on an individual basis to reduce asymmetry by targeting the force-velocity curve.